Static properties of quasi-confined hard-sphere fluids. (23rd August 2019) - Petersen, Charlotte F; Schrack, Lukas; Franosch, Thomas
Abstract: Confined fluids display complex behavior due to layering and local packing. Here, we disentangle these effects by confining a hard-sphere fluid to the surface of a cylinder, such the circumference extends only over a few particle diameters. We compare the static structure factor and the pressure measured in computer simulations to the Percus–Yevick closure in liquid state theory. A non-monotonic evolution of the static-structure-factor peak and the pressure is observed upon variation of the confining length, similar to a liquid confined between two plates. This indicates that the density profile and the particle correlations may not be intrinsically connected in real confined liquids.